REGγ accelerates melanoma formation by regulating Wnt/β‐catenin signalling pathway. Issue 11 (30th August 2017) - Chen, Hui; Gao, Xiao; Sun, Zhengwang; Wang, Qingwei; Zuo, Di; Pan, Linian; Li, Kun; Chen, Jiwei; Chen, Geng; Hu, Kewen; Li, Ke; Shah, Abdus Saboor; et al.
Abstract: It has been reported that the proteasome activator REGγ is associated with multiple oncogenic pathways in human cancers. However, the role of REGγ in the development of melanoma and the underlying mechanisms remain unclear. In this study, we attempted to investigate the effects of REGγ on human melanoma cell proliferation in vitro and in vivo. We demonstrated that knockdown of REGγ inhibited melanoma cell growth and arrested melanoma cell at G1 phase. Furthermore, depletion of REGγ also inhibited the xenograft growth of human melanoma. Mechanistically, REGγ activates Wnt/β‐catenin signal pathway by degrading GSK‐3β in melanoma cell lines and mouse models. Transient knockdown of β‐catenin effectively blocked cell proliferation in REGγ wild‐type melanoma cells. In human melanoma samples, REGγ was overexpressed and positively correlated with β‐catenin levels. This study demonstrates that REGγ is a central molecule in the development of melanoma by regulating Wnt/β‐catenin pathway. This suggests that targeting REGγ could be an alternative therapeutic approach for melanoma.